Analisis Gaya Bahasa Dalam Cerpen The Oval Portrait Karya Edgar Allan Poe - Sri Arfani (LPPM Universitas Bina Sarana Informatika, 2015)
Analysis of figure of speeh. This research aims to describe the figure of speech used by EDGAR ALLAN POE in the short story THE OVAL PORTRAIT. This research used is descriptive method in form of qualitative by using structural and stylistics approach. Based on the result of the data analysis, the conclusions of this research that there are four type of figure of speech was found in short story of THE OVAL PORTRAIT by EDGAR ALLAN POE. The data was shown there are six examples of phrases figure of speech namely: 1) methaphore was found in this short story only 1 phrase, 2) simily was found in this short story consist of 2 phrases,3) alliteration was foundin this short story is 2 phrases, and 4) irony was found only 1 phrase. The authors were able to create a better sense to the reader by explaining things in this short story, using stylistic way.